2005
DOI: 10.1007/s10450-005-6037-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Photocatalytic Decomposition of Volatile Organic Compounds on Photocatalyst of TiO2—Silica Beads

Abstract: Photocatalyst of TiO 2 coated on silica beads was prepared, and the adsorption isotherms and kinetics of photocatalytic decomposition of acetone and acetaldehyde on the photocatalyst were studied at room temperature (ca. 298 K). Adsorption isotherms of both acetone and acetaldehyde conformed to the Langmuir isotherm. FTIR spectra of the gas phase showed that these volatile organic compounds were mainly oxidized to CO 2 and H 2 O. The time courses of concentration change due to photocatalytic decomposition unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
6
1
Order By: Relevance
“…Coronado et al [26] reported the adsorption constant of acetone for the weak sites of TiO 2 thin film was 0.2 m 3 /g and 0.046 m 3 /g for RH = 0% and 25%, respectively. Tomida et al [16] investigated the adsorption isotherms of acetone on the photocatalyst of TiO 2 coated on silica beads and obtained similar results. All the reported adsorption coefficient values are at the same order of magnitude as those obtained in this study.…”
Section: Adsorption Coefficients Verificationsupporting
confidence: 53%
See 1 more Smart Citation
“…Coronado et al [26] reported the adsorption constant of acetone for the weak sites of TiO 2 thin film was 0.2 m 3 /g and 0.046 m 3 /g for RH = 0% and 25%, respectively. Tomida et al [16] investigated the adsorption isotherms of acetone on the photocatalyst of TiO 2 coated on silica beads and obtained similar results. All the reported adsorption coefficient values are at the same order of magnitude as those obtained in this study.…”
Section: Adsorption Coefficients Verificationsupporting
confidence: 53%
“…In fact the values derived from a kinetic study are usually much higher than those obtained from the Langmuir adsorption isotherm in the absence of light [3]. In few articles relevant to the adsorption isotherms [15][16][17][18], the adsorption performance was examined with a limited number of compounds of interest, such as toluene, acetone, and trichloroethylene. Moreover, the effect of relative humidity on adsorption isotherms has not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies exist that deconvolute the adsorption and desorption processes involving the acetone−TiO 2 system from the reactive pathways, ,, those experiments employed acetone partial pressures that are several orders of magnitude above those found indoors. For example, in adsorption and desorption studies reported by El-Maazawi et al, who employed equilibrium acetone concentrations between 0.1 and 1.5 Torr, it was noted that the uptake data did not follow a simple Langmuir model.…”
Section: Introductionmentioning
confidence: 99%
“…But the peak area assigned to acetaldehyde decrease did not almost. Because the introduced acetaldehyde was a big enough amount for the photocatalyst [18], and the peak assigned to carbon dioxide was not observed, these results that indicate these IR spectra correspond to the first decomposition step of acetaldehyde. Fig.…”
Section: Decomposition Of Acetaldehydementioning
confidence: 50%